OP0092 Indicators of Depression are Stronger Predictors of Work Disability in Early Arthritis than Disease Activity or Response to Therapy. (23rd January 2014) - Westhoff, G.; Callhoff, J.; Schneider, M.; Zink, A.
Abstract : Background: The decision to stop working in patients with early inflammatory arthritis (IA) is influenced by a wide range of factors besides arthritis disease activity. Objectives: To assess the association between patients' characteristics at arthritis onset and the consideration or decision to request disability pension within the first 12 months of rheumatologic care. Methods: 501 gainfully employed patients ≤63 years of age enrolled in an early IA cohort (<6 months) were analyzed with respect to their consideration to go for early retirement within the first 12 months of rheumatologic care. Independent variables in multivariate logistic regression were sex, education (3 groups), baseline body mass index (BMI <25, 25-30, >30), RF and/or ACPA serology (negative, low-positive, high-positive), acute phase reactants (CRP and ESR normal, CRP or ESR abnormal), tender and swollen joint counts (T/SJC28 0-3, 4-10, >10), and 12 physician reported common chronic conditions (yes/no). Patient-reported parameters included pain, morning stiffness, fatigue (VAS 0-3, 4-6, 7-10), functional capacity (FFbH 3 groups) and the first item of the Patient Health Questionnaire Depression scale (PHQ9):"Having little pleasure or interest in doing things during the last two weeks" (not at all, on several days, more than half of the days). The analysis was adjusted for age (continuous) and improvement of disease activity within 12 months (EULAR response: good, moderate, no response). Results: Patients (67% female) were 47 ±10 years old and had symptom duration of 13 ±7 weeks. 67% were RF and/or ACPA positive and 65% fulfilled the new ACR-EULAR RA criteria at baseline. 87% took DMARDs at 12 months. At 12 months, 36 of the patients were considering applying for early retirement, 14 had applied and 12 had gone into early retirement (∑ 62; 12.4%). These 62 patients compared in formal education but were about 6 years older (53 vs. 47 years) and had significantly higher disease activity and severity, especially worse fatigue, within the first year (not shown). However, none of the arthritis activity measures or any of the considered cardiovascular, metabolic or pulmonary diseases was associated with early retirement in multivariate analysis. Instead, the highest association was found with "having little pleasure or interest in doing things most of the days" (Table). Overall, 10.6% of the patients reported that problem; 30% of them were considering early retirement or had gone into. The complete 9-item depression score confirmed these findings. Image/graph: Conclusions: Whether or not patients with early arthritis are considering applying for disability pension depends more on mental conditions than on disease activity. Since one single depression statement was able to identify patients with an increased risk of early retirement, well-directed attention on the patient's well-being in the early stages of the disease may help the patients to remain in the labour force. Disclosure of Interest: None Declared